Clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9-generated diallelic mutants reveal Arabidopsis actin-related protein 2 function in the trafficking of syntaxin PEN1 - Gao, Peng; Qin, Li; Nguyen, Hanh; Sheng, Huajin; Quilichini, Teagen D.; Xiang, Daoquan; Kochian, Leon V.; Wei, Yangdou; Datla, Raju (Frontiers in Plant Science, 2022)
In plants, the actin cytoskeleton plays a critical role in defense against diverse pathogens. The formation of actin patches is essential for the intracellular transport of organelles and molecules towards pathogen penetration sites and the formation of papillae for an early cellular response to powdery mildew attack in Arabidopsis thaliana. This response process is regulated by the actin-related protein (ARP)2/3 complex and its activator, the WAVE/SCAR complex (W/SRC). The ARP2/3 complex is also required for maintaining steady-state levels of the defense-associated protein, PENETRATION 1 (PEN1), at the plasma membrane and for its deposition into papillae. However, specific ARP2 functionalities in this context remain unresolved, as knockout mutants expressing GFP-PEN1 reporter constructs could not be obtained by conventional crossing approaches. In this study, employing a CRISPR/Cas9 multiplexing-mediated genome editing approach, we produced an ARP2 knockout expressing the GFP-PEN1 marker in Arabidopsis. This study successfully identified diallelic somatic mutations with both ARP2 alleles edited among the primary T1 transgenic plants, and also obtained independent lines with stable arp2/arp2 mutations in T2 generation. Further analyses on these arp2/arp2 mutants showed similar biological functions of ARP2 to ARP3 in the accumulation of PEN1 against fungal invasion. Together, this CRISPR/Cas9-based approach offers highly efficient simultaneous disruption of the two ARP2 alleles in GFP-PEN1-expressing lines, and a rapid method for performing live-cell imaging to facilitate the investigation of important plant-pathogen interactions using a well-established and widely applied GFP marker system, thus gaining insights and elucidating the contributions of ARP2 upon fungal attack.